Cereal grain-based functional foods : carbohydrate and phytochemical components - Beta, Trust; Camire, Mary Ellen (Royal Society of Chemistry, 2019)
Detailed coverage of the composition and functionality of the bulk carbohydrate components and the trace phytochemical components, i.e. phenolic compounds in cereal grains and grain products, is provided for researchers, clinicians and students.
Title from title details screen.
Keywords: Grain.; Functional foods.; elektronické knihy; electronic books